Pengaruh Etika Bisnis Islam Terhadap Kesetiaan Pelanggan Di Koperasi Jaya Abadi Tubanan Kembang Jepara - aditianto, ahmad roif; Arifin, Samsul (ITB AAS INDONESIA Surakarta, 2024)
This research aims to analyze the influence of Islamic business ethics on customer loyalty at the Jaya Abadi Tubanan Kembang Jepara Cooperative through the variables customer commitment trust and relationship benefits. The population in this study was 844 members of the Jaya Abadi Tubanan Kembang Jepara Cooperative. Sampling used the Incidental Sampling technique with the selected criteria being 90 customers. The results of the research show that in Islamic business ethics the customer loyalty at the Jaya Abadi Tubanan Kembang Jepara Cooperative is (1) Customer commitment has no effect on Customer Loyalty. This could happen because the commitment in the questionnaire is about the Bank's service to customers, which can give rise to different perceptions for each customer. (2) Trust has a significant effect on customer loyalty because customers receive transaction protection and obtain their rights in transactions. (3) Relational Benefits have a significant effect on customer loyalty because customers receive service benefits such as a sense of security and calm. (4) Simultaneously Customer commitment, Trust, Relationship benefits have a significant effect on Customer Loyalty as seen from the ANOVA test results thatiatheiacalculated F value is 13.48 while the F table value is 2.70 and the significanceiavalue is 0.000